Characterization of Triple Negative Breast Cancer - Bernardo Enrique Heredia Martínez; Hailyn González Fernández (Revista Finlay, 2020)
Background: triple negative breast cancer constitutes a public health problem due to its high morbidity and mortality. Objective: to characterize the patients diagnosed with triple negative breast cancer treated at the Oncology Service of the Celestino Hernández Robau University Hospital in the period 2015-2016. Method: a descriptive cross-sectional study was carried out. The universe corresponded to 59 patients diagnosed with histological confirmed triple negative breast cancer. The variables were considered: age, skin color, histological variant, tumor size, lymph node status, vascular and lymphatic invasion, histological grade and clinical nucleo-stages, treatment, type and time of appearance of metastases. The information collected was processed through the statistical program IBM SPSS version 21. The frequency and percentage distributions were used from descriptive statistics. The results were expressed by charts. Results: the predominant age group was 60 and over, white skin color, the most frequent histological diagnosis was infiltrating ductal carcinoma, clinical stage II prevailed, there was no involvement of axillary lymph nodes or vascular and lymphatic invasion, the diagnosed metastases that the visceral ones predominated. Conclusions: the age of 60 years and older prevailed and infiltrating ductal carcinoma, tumor size, histological grade and nuclear grade are important prognostic factors for the diagnosis and treatment of triple negative breast cancer. At the end of the study, the 55,9 % of the patients were alive.